CONTROLE PHYSICO-CHIMIQUE DU PRODUIT FINI DICLOFENAC SODIUM - Nour Benkedjouh (My University, 2026)
This work focuses on the study and evaluation of the quality control process for the finished pharmaceutical product Xinac®0.1%, an ophthalmic solution containing diclofenac sodium. The research was conducted at the GENERICLAB laboratories in Algeria. The main goal was to assess the product's compliance with international Pharmacopoeia standards and internal company specifications. The experimental phase involved a series of physico-chemical tests (appearance, density, pH, osmolarity) and the precise quantification of the active ingredient and the preservative (benzalkonium chloride) using High-Performance Liquid Chromatography (HPLC). The findings demonstrated full compliance across all parameters, confirming the reliability of the manufacturing process and the overall quality of the product ---------------------------------------------------------------- يركز هذا العمل على دراسة وتقييم عملية الرقابة على الجودة للمنتج الصيدلاني النهائي Xinac®0.1%، وهو عبارة عن قطرة عين تعتمد على المادة الفعالة ديكلوفيناك الصوديوم. تم إجراء الدراسة في مختبرات شركة GENERICLAB بالجزائر، ويهدف البحث إلى التأكد من مطابقة المنتج للمعايير الدولية والمواصفات الداخلية للشركة. شملت الدراسة إجراء سلسلة من الاختبارات الفيزيائية والكيميائية )المظهر، الكثافة، الُأس الهيدروجيني pH، والأسمولية(، بالإضافة إلى استخدام تقنية الكروماتوغرافيا السائلة عالية الأداء (HPLC) لتحديد هوية وتركيز المادة الفعالة والمادة الحافظة )بنزالكونيوم كلوريد.( أظهرت النتائج أن جميع الاختبارات كانت مطابقة للمواصفات، مما يؤكد سلامة وفعالية المنتج وجودة عملية التصنيع -------------------------------------------------------------- Ce travail porte sur l'étude et l'évaluation du processus de contrôle qualité du produit fini Xinac®0.1%, un collyre à base de diclofénac sodique utilisé en ophtalmologie. L'étude a été réalisée au sein des laboratoires de l'entreprise GENERICLAB en Algérie. L'objectif principal était de vérifier la conformité du produit aux normes de la Pharmacopée et aux spécifications internes. Le protocole expérimental a inclus des tests physico-chimiques (aspect, densité, pH, osmolarité) ainsi que le dosage du principe actif et du conservateur (chlorure de benzalkonium) par la technique de Chromatographie Liquide Haute Performance (HPLC). Les résultats obtenus ont révélé une parfaite conformité, garantissant ainsi la stabilité, l'efficacité et la sécurité du médicament pour le patient
Keywords: Quality control; Diclofenac sodium; Xinac®0.1%; Eye drops; HPLC.; الرقابة على الجودة، ديكلوفيناك الصوديوم، Xinac®0.1%، قطرة عين، HPLC; Contrôle qualité; Diclofénac sodique; Collyre; HPLC